The origin of pesisir cattle based on D-loop mitochondrial DNA - Anzalia Eka Putri; ACHMAD FARAJALLAH; DYAH PERWITASARI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Putri AE, Farajallah A, Perwitasari D. 2019. The origin of pesisir cattle based on D-loop mitochondrial DNA. Biodiversitas 20: 2569-2575. Pesisir cattle is one of Indonesia's local cattle descended from Bos indicus which has small body characteristics. It was assumed due to crossbreeding between pesisir cattle and other cattle. Therefore this study aims to study the origin of pesisir cattle based on the D-loop mtDNA region and to find out the phylogenetic relationships between pesisir cattle and other cattle. Cattle blood samples were taken in two locations, Krui Way and Tanah Rekah. Amplification of the mitochondrial gene using the primary pair of collections of Dr. Achmad Farajallah, namely AF22 (forward) 5'-GCGTACGCAATCTTACGATCA-3' and AF23 (reverse) 5'-ATGCAGTTAAGTCCAGCTAC-3'. Reconstruction of phylogenetic trees was analyzed using the Neighbor-Joining Method based on Kimura 2 Parameters. The results of the mtDNA analysis in the D-loop region showed that there were two broods in pesisir cattle, namely Bos indicus and Bos javanicus. The closeness between these species is due to the close geographical distance between Bos indicus originating from Way Krui, Lampung and Bos javanicus from Java.